Pastoral Community Malaria Prevention Practice and Associated Factors Among Households in Three Districts of the Borena Zone, Southern Ethiopia - Alqeer Aliyo; Wako Golicha; Anteneh Fikrie (SAGE Publishing, 2023)
Background Malaria infection remains one of the major global and national public health threats, affecting millions of people yearly by causing substantial morbidity and mortality. In developing countries, higher proportions of poor malaria prevention and control measure both regionally and nationally, particularly in pastoral community areas of southern Ethiopia. Objective The study aimed to assess malaria preventive practices and associated factors among households of pastoral communities in Borena zone, Oromia regional state, Southern Ethiopia, 2022. Methodology A community-based cross-sectional study design was used from March first to 30, 2022, among 421 selected simple random sampling households in pastoral communities of the Borena zone. Data were collected through face-to-face interviews with a structured pretested questionnaire and visual observation for household malaria prevention practices. Then, the data were analyzed using SPSS version 25. Bivariate and multivariable logistic regression analyses were used to identify factors associated with malaria preventive practices. Finally, adjusted odd ratio (AOR) together with 95% confidence intervals was used, and a P value of less than 0.05 indicated an overall statistical association. Result The overall malaria prevention rate among pastoral community households was 31.6%(133) [95%; CI = 27.2-36.4]. The factors significantly associated with malaria prevention practice were malaria prevention knowledge [AOR = 1.6, 95% CI = 1.1-2.5] and the absence of plasmodium parasites among children [AOR = 4.3, 95% CI = 2.8-8.7]. However, households staying outdoors at night [AOR = 0.5, 95% CI = 0.3-1.0] were negatively associated with household malaria prevention. A total of 200 (47.5%) households had used insecticide-treated mosquito nets (ITN) and 5(1.2%) households had indoor residual sprays (IRS). Conclusion The study revealed lower malaria prevention practices among households of the pastoral community. The government and other concerned bodies should contribute to malaria prevention measures in pastoral remote areas. Health extension workers should have to create awareness in the communities to avoid incorrect use of the ITN.